2021
DOI: 10.1021/acsami.1c10043
|View full text |Cite
|
Sign up to set email alerts
|

Couple of Nonpolarized/Polarized Electrodes Building a New Universal Electrochemical Energy Storage System with an Impressive Energy Density

Abstract: Herein, we propose a new concept of energy storage system composed of a nonpolarized electrode and a polarized electrode (PPE) with an impressive energy density. It offered nearly 4 times higher energy density than that of carbon-based supercapacitor. Among the suggested potential PPE system, we introduced an electrodeposited nanozinc on the copper foam as the nearly nonpolarized electrode and a Zn-2,5dihydroxyterephthalic acid (DHTA) metal−organic framework (MOF)derived activated porous carbon as a nearly pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…7 MOFs also have potential in photocatalysis, 8 electrocatalysis, 9 chemiresistive sensing, 10 and energy storage technologies. 11 In these applications, identifying MOFs with superior electrical conductivity and flexible structure has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 MOFs also have potential in photocatalysis, 8 electrocatalysis, 9 chemiresistive sensing, 10 and energy storage technologies. 11 In these applications, identifying MOFs with superior electrical conductivity and flexible structure has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent porosity and surface area (access to 7140 m 2 /g 3 ), early studies in MOFs were primarily focused on separation, , gas storage, clinical services, and catalysis . MOFs also have potential in photocatalysis, electrocatalysis, chemiresistive sensing, and energy storage technologies . In these applications, identifying MOFs with superior electrical conductivity and flexible structure has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen evolution from water can be an effective strategy to deal with the energy crisis in the current conditions, where the shortage of energy and environmental pollution have challenged the world. , The replacement of nonrenewable energies with clean hydrogen energy can potentially address the challenges faced globally. , Scientists have examined different procedures for H 2 production, including the development of various semiconductor-based photocatalysts like oxides, sulfides, oxynitrides, and nanocomposites, since Fujishima and Honda discovered TiO 2 photocatalysts. , Yet, the commercial applications of metal oxides are mainly limited considering the flash recombination of photoexcited electron–hole pairs . Advanced photocatalysts are currently based on materials with a shorter synthesis pathway and less energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials mainly include porous carbon, CNT, and GO, and among them, activated carbon has the advantages of a simple preparation process, abundant pore size, large specific surface area, etc. [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials mainly include porous carbon, CNT, and GO, and among them, activated carbon has the advantages of a simple preparation process, abundant pore size, large specific surface area, etc. [2] .A large number of studies have been reported on activated carbon as electrode materials for supercapacitors. However, the disadvantage of using AC as a supercapacitor electrode material is that the energy density is relatively low (about 5-10 Whkg -1 ).…”
mentioning
confidence: 99%